Amount and Type of Dietary Fat, Postprandial Glycemia, and Insulin Requirements in Type 1 Diabetes: A Randomized Within-Subject Trial - Bell, Kirstine J.; Fio, Chantelle Z.; Twigg, Stephen; Duke, Sally-Anne; Fulcher, Gregory; Alexander, Kylie; McGill, Margaret; Wong, Jencia; Brand-Miller, Jennie; Steil, Garry M. (Diabetes care, 2020)
The American Diabetes Association recommends individuals with type 1 diabetes (T1D) adjust insulin for dietary fat; however, optimal adjustments are not known. This study aimed to determine ) the relationship between the amount and type of dietary fat and glycemia and ) the optimal insulin adjustments for dietary fat. Adults with T1D using insulin pump therapy attended the research clinic on 9-12 occasions. On the first six visits, participants consumed meals containing 45 g carbohydrate with 0 g, 20 g, 40 g, or 60 g fat and either saturated, monounsaturated, or polyunsaturated fat. Insulin was dosed using individual insulin/carbohydrate ratio as a dual-wave 50/50% over 2 h. On subsequent visits, participants repeated the 20-60-g fat meals with the insulin dose estimated using a model predictive bolus, up to twice per meal, until glycemic control was achieved. With the same insulin dose, increasing the amount of fat resulted in a significant dose-dependent reduction in incremental area under the curve for glucose (iAUC ) in the early postprandial period (0-2 h; = 0.008) and increase in iAUC in the late postprandial period (2-5 h; = 0.004). The type of fat made no significant difference to the 5-h iAUC . To achieve glycemic control, on average participants required dual-wave insulin bolus: for 20 g fat, +6% insulin, 74/26% over 73 min; 40 g fat, +6% insulin, 63/37% over 75 min; and 60 g fat, +21% insulin, 49/51% over 105 min. This study provides clinical guidance for mealtime insulin dosing recommendations for dietary fat in T1D.